Development of CBCS Evaluation Model by using Machine Learning Technique - Kumar Miri, Santosh (International Journal of Computer Sciences and Engineering, 2024)
The CBCS (Choice Based Credit System) is a grading system that provides an opportunity for the students to select courses from the prescribed courses. It provides flexibility in designing curriculum. It assigns credits based on the course content and hours of teaching. The prescribed courses can be core, elective/minor or skill-based courses. The students earn credits based on their performance. The CBCS Evaluation Model is a model for the design, development and evaluation of student-centered instructional paradigm by using Machine Learning Technique. It provides a cross-cultural learning environment for the development of quality education. It upgrades educational and occupational aspiration of the upcoming generation of the higher education.